2019
DOI: 10.1021/acs.chemmater.9b00546
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atomistic Substitution on Thin-Film Structure and Charge Transport in a Germanyl-ethynyl Functionalized Pentacene

Abstract: Functionalization of organic semiconductors through the attachment of bulky side groups to the conjugated core has imparted solution processability to this class of otherwise insoluble materials. A consequence of this functionalization is that the bulky side groups impact the solid-state packing of these materials. To examine the importance of side-group electronic character on accessing the structural phase space of functionalized materials, germanium was substituted for silicon in triisopropyl­silylethynyl­p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
163
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(173 citation statements)
references
References 49 publications
6
163
3
1
Order By: Relevance
“…With a better understanding of the molecular origin of cooperative transition, we can formulate molecular design rules to trigger cooperativity for future applications in organic electronics and molecular devices. We also emphasize the importance of the dynamics of side-chains beyond phase transitions of molecular crystals, as previous works have shown that slight modulation of side-chains can lead to drastic differences in various properties, such as molecular packing 15 and mechanical properties. 38,39 In this work, we further investigate the hypothesis that sidechain rotation is a molecular design rule for cooperative transition and demonstrate that the polymorphic transition mechanism is sensitive to even a single atom substitution.…”
mentioning
confidence: 77%
“…With a better understanding of the molecular origin of cooperative transition, we can formulate molecular design rules to trigger cooperativity for future applications in organic electronics and molecular devices. We also emphasize the importance of the dynamics of side-chains beyond phase transitions of molecular crystals, as previous works have shown that slight modulation of side-chains can lead to drastic differences in various properties, such as molecular packing 15 and mechanical properties. 38,39 In this work, we further investigate the hypothesis that sidechain rotation is a molecular design rule for cooperative transition and demonstrate that the polymorphic transition mechanism is sensitive to even a single atom substitution.…”
mentioning
confidence: 77%
“…Predicting crystal structures and packing motifs of such van der Waals bound molecular solids is also difficult since small molecular modifications can induce drastic changes of the packing motifs, leading to significantly altered optoelectronic solid-state properties. [4,[6][7][8][9] Among the organic semiconductors (OSC), acenes are frequently studied because their aromatic frame enables versatile control of the electronic structure through their topology (e.g. length, branching, etc.)…”
mentioning
confidence: 99%
“…Crystal engineering, the design of a crystal structure with a specified topology of molecules, or a specified property, is extremely challenging, because the interplay of new intermolecular interactions is still not sufficiently understood. 22 Previous approaches to screen small molecules for their potential suitability as OSCs include data mining approaches, 23 atomistic substitutions, 24 and machine-learning approaches. 25,26 Kunkel et al screened the Cambridge Structural Database (CSD) to obtain statistically significant structure-property relationships with certain scaffolds (side groups) leading to consistently improved charge-transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…25 The specific concept of atomistic substitution leading to a modified polymorphic landscape and thus changed charge transport behaviour has been experimentally investigated by Sorli et al via the study of germanyl-ethynyl functionalised pentacene compared to TIPS-pentacene. 24 We are particularly interested in small helicene molecules for potential applications as organic semiconducting materials. Helicenes are axially chiral fused benzene rings (Fig.…”
Section: Introductionmentioning
confidence: 99%